Estudio del efecto del mesocarpio del coco y estiércol bovino en la conductividad térmica y resistencia a la compresión de bloques de mampostería (2020)
This research paper carried out thermal conductivity measurement tests in accordance with ASTM C 177 (2013). Blocks were composed of mortar, bovine manure and coconut fiber where the bovine manure was adjusted by a maximum of 10% and 1,5% coconut fiber of the total volume of sand used in the block. Subsequently, compression resistance tests were performed and the percentage of moisture absorption and density was evaluated under ASTM C140. First of all, the individual amounts that make up a block in terms of cement, water and sand were calculated. An experimental design determined the quantities of specimens to be manufactured between blocks and plates for thermal conductivity assessment. For the preparation of the materials, a process of crushing and drying the manure as well as drying to the coconut fiber was carried out. Then the manufacture of the blocks and plates under the above-mentioned standards was completed. The results obtained were that manure reduced the coefficient of thermal conductivity by 50% when replaced by 10% and 1,5% coconut fiber with respect to a control plate. In terms of coconut fiber with percentages of 0,5; 1 and 1,5%, they gave greater compression resistance results than a control block (block containing no material other than its natural composition). It is worth noting the blocks with percentages of coconut fiber 0,5%, coconut fiber 1%, coconut fiber 1,5% and bovine manure 3% with coconut fiber 1,5% meet the compression resistance requirements set out in ASTM C129-17